2015
DOI: 10.1111/gcb.12976
|View full text |Cite
|
Sign up to set email alerts
|

Woodland recovery following drought‐induced tree mortality across an environmental stress gradient

Abstract: Recent droughts and increasing temperatures have resulted in extensive tree mortality across the globe. Understanding the environmental controls on tree regeneration following these drought events will allow for better predictions of how these ecosystems may shift under a warmer, drier climate. Within the widely distributed piñon-juniper woodlands of the southwestern USA, a multiyear drought in 2002-2004 resulted in extensive adult piñon mortality and shifted adult woodland composition to a juniper-dominated, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
50
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 39 publications
(52 citation statements)
references
References 63 publications
2
50
0
Order By: Relevance
“…Similarly, Redmond et al . () found that Pinus edulis juveniles had lower mortality beneath dead pinyons than canopy interspaces; however, they did not document mortality under living pinyons.…”
Section: Discussionmentioning
confidence: 88%
“…Similarly, Redmond et al . () found that Pinus edulis juveniles had lower mortality beneath dead pinyons than canopy interspaces; however, they did not document mortality under living pinyons.…”
Section: Discussionmentioning
confidence: 88%
“…In a consistent manner, studies have shown positive effects of artificial shade or neighbouring vegetation on early conifer seedling survival (Baumeister & Callaway, ; Haugo, Bakker, & Halpern, ; Keyes et al., ; Perkins, ), although dense shrubs after high‐severity fire can be associated with reduced conifer regeneration or growth (Crotteau, Varner, & Ritchie, ; Tepley et al., ). Grass and herb cover, however, more consistently decrease conifer seedling survival (Harmon & Franklin, ; Perkins, ; Redmond, Cobb, Clifford, & Barger, ), likely due to the combination of reduced light and more efficient competition for below‐ground resources by the fibrous roots of grasses in surface layers. Similar to nutrients, faster‐growing deciduous species tend to respond more positively to light availability than conifers (Calder et al., ).…”
Section: Demographic Filters Determine Postfire Vegetation Communitiesmentioning
confidence: 99%
“…However, care must be taken to avoid confounding effects of the infrastructure (e.g., striping, shading) and disturbance during data collection activities. Plant community changes can have cascading effects on other biotic interactions (e.g., herbivory, pests and pathogens, invasive species, insect dispersers or pollinators), as well feedbacks to faunal communities (Caldeira et al., ; Redmond, Cobb, Clifford, & Barger, ).…”
Section: Selecting Response Variables and Measurement Techniquesmentioning
confidence: 99%